Role of BH4 deficiency as a mediator of oxidative stress-related endothelial dysfunction in menopausal women - DuBose, Lyndsey E; Ozemek, Cemal; Wick, Tyler; Richardson, Vanessa; Hildreth, Kerry L; Moreau, Kerrie L (American journal of physiology. Heart and circulatory physiology, 2022)
Endothelial function (brachial artery flow-mediated dilation [FMD]) is reduced in estrogen-deficient postmenopausal women, mediated, in part, by reduced nitric oxide (NO) bioavailability, secondary to tetrahydrobiopterin (BH4) deficiency and oxidative stress. FMD is increased, but not fully restored, in postmenopausal women after acute intravenous vitamin C (VITC; superoxide scavenger) or oral BH4 supplementation. In vitro studies demonstrate that coadministration of VITC with BH4 prevents endothelial nitric oxide synthase (eNOS) uncoupling and reductions in NO by peroxynitrite. To investigate mechanisms of endothelial dysfunction in women, we assessed the separate and combined effects of VITC and BH4 to determine whether coadministration of VITC + BH4 improves FMD in healthy postmenopausal women (n = 19, 58 ± 5 yr) to premenopausal (n = 14, 36 ± 9 yr) levels, with exploratory testing in perimenopausal women (n = 8, 51 ± 3 yr). FMD was measured during acute intravenous infusions of saline (control) and VITC (∼2-3 g) ∼3 h after a single dose of oral BH4 (KUVAN, 10 mg/kg body wt) or placebo (randomized crossover, separated by ∼1 mo). Under the placebo condition, FMD was reduced in postmenopausal compared with premenopausal women during the saline infusion (5.6 ± 0.7 vs. 11.6 ± 0.9%, P < 0.001) and increased in postmenopausal women during VITC (+3.5 [1.4, 5.6]%, P = 0.001) and acute BH4 (+1.8 [0.37, 3.2]%, P = 0.01) alone. Coadministration of VITC + BH4 increased FMD in postmenopausal women (+3.0 [1.7, 4.3]%, P < 0.001), but FMD remained reduced compared with premenopausal women (P = 0.02). Exploratory analyses revealed that VITC + BH4 did not restore FMD in perimenopausal women to premenopausal levels (P = 0.045). Coadministration of VITC + BH4 does not restore FMD in menopausal women, suggesting that additional mechanisms may be involved.NEW & NOTEWORTHY Endothelial function is reduced across the menopausal stages related to increased oxidative stress associated with estrogen deficiency. In vitro studies demonstrate that coadministration of VITC with BH4 prevents endothelial nitric oxide synthase (eNOS) uncoupling and reductions in NO by peroxynitrite; however, this remains untested in humans. We demonstrate that the coadministration of BH4 + VITC does not restore endothelial function in perimenopausal and postmenopausal women to the level of premenopausal women, suggesting that other mechanisms contribute.Endothelial function (brachial artery flow-mediated dilation [FMD]) is reduced in estrogen-deficient postmenopausal women, mediated, in part, by reduced nitric oxide (NO) bioavailability, secondary to tetrahydrobiopterin (BH4) deficiency and oxidative stress. FMD is increased, but not fully restored, in postmenopausal women after acute intravenous vitamin C (VITC; superoxide scavenger) or oral BH4 supplementation. In vitro studies demonstrate that coadministration of VITC with BH4 prevents endothelial nitric oxide synthase (eNOS) uncoupling and reductions in NO by peroxynitrite. To investigate mechanisms of endothelial dysfunction in women, we assessed the separate and combined effects of VITC and BH4 to determine whether coadministration of VITC + BH4 improves FMD in healthy postmenopausal women (n = 19, 58 ± 5 yr) to premenopausal (n = 14, 36 ± 9 yr) levels, with exploratory testing in perimenopausal women (n = 8, 51 ± 3 yr). FMD was measured during acute intravenous infusions of saline (control) and VITC (∼2-3 g) ∼3 h after a single dose of oral BH4 (KUVAN, 10 mg/kg body wt) or placebo (randomized crossover, separated by ∼1 mo). Under the placebo condition, FMD was reduced in postmenopausal compared with premenopausal women during the saline infusion (5.6 ± 0.7 vs. 11.6 ± 0.9%, P < 0.001) and increased in postmenopausal women during VITC (+3.5 [1.4, 5.6]%, P = 0.001) and acute BH4 (+1.8 [0.37, 3.2]%, P = 0.01) alone. Coadministration of VITC + BH4 increased FMD in postmenopausal women (+3.0 [1.7, 4.3]%, P < 0.001), but FMD remained reduced compared with premenopausal women (P = 0.02). Exploratory analyses revealed that VITC + BH4 did not restore FMD in perimenopausal women to premenopausal levels (P = 0.045). Coadministration of VITC + BH4 does not restore FMD in menopausal women, suggesting that additional mechanisms may be involved.NEW & NOTEWORTHY Endothelial function is reduced across the menopausal stages related to increased oxidative stress associated with estrogen deficiency. In vitro studies demonstrate that coadministration of VITC with BH4 prevents endothelial nitric oxide synthase (eNOS) uncoupling and reductions in NO by peroxynitrite; however, this remains untested in humans. We demonstrate that the coadministration of BH4 + VITC does not restore endothelial function in perimenopausal and postmenopausal women to the level of premenopausal women, suggesting that other mechanisms contribute.